Introducing Java EE 7 : a look at what's new - Juneau, Josh (Apress Imprint: Apress, 2013)
Introducing Java EE 7:  A Look at What's New guides you through the new features and enhancements in each of the technologies comprising the Java EE platform.  Readers of this book will not have to wade through introductory material or information covering features that have been part of the EE platform for years.  Instead, developers can pick this book up and read it to brush up on those features that have changed or have been added for the EE 7 release.  This handy reference helps you move forward from Java EE 6 to the new EE 7 platform quickly and easily. Java is a mature programming language that has been refined over the years into a productive language widely used in enterprise application development.  Although the language contains frameworks and methodologies that have been used for years, it is important to make use of the most current features available in the language in order to achieve the best results.  Introducing Java EE 7:  A Look at What's New covers the solutions using the most current Java Enterprise technologies, including EJB 3.2, JSF 2.2, and JAX-RS 2.0.  Build a streamlined and reliable application that uses the latest in Java technologies, and develop it much faster than you did with the older technologies.  Rejuvenate your Java expertise to use the freshest capabilities, or perhaps learn Java Enterprise development for the first time and discover one of the most widely used and most powerful technologies available for application development today.  Get up and running quickly with the new features of EE 7! Designed to get you up and running quickly with the newly released Java EE 7 Includes real world examples of how to use new and updated features. Demonstrates the latest productivity enhancements in the platform